Influence of complex chemical additives on the water resistant silicate materials - Hryhorenko Olena; Lobanova Anastasia; Kazimagomedov Ibrahim; Plakhotnikov Kyrylo; Lulyko Olexandr (MATEC Web of Conferences, 2017)
In this paper, it has been established that the use of silica fume, low-base slag and calcium hydroxide to modify clays in constrained contact conditions leads to an increase in the number of contacts between the particle components and provides the conditions for the formation of strong contacts and the formation of dense microstructures, and therefore reduces its water absorption and increases water resistance of unburned building materials based on local aluminum silicate raw materials.